Ethical Responsibility of Teachers and Students from a Humanistic Perspective - Luis Guillermo Barrantes-Montero (Revista Electrónica Educare)
This paper provides some considerations on the importance of ethical responsibility in higher education institutions for both teachers and students. Its purpose is to identify the causes of corrupt behavior in some university graduates once they become part of the labor force or public service. It also points out some ways through which an ethical worldview can be formed and promoted in society. It is concluded that education, seen as a privilege and as a commitment, leads to the virtue of gratitude and, consequently, to a humanistic ethical behavior.